Medieval literature: an introduction to type-scenes - Battles, Dominique 1964- (New York, USA: Routledge, 2025)
"Medieval Literature: An Introduction to Type-Scenes is the first book-length exploration of the type-scenes of western medieval literature from the ninth to the fifteenth centuries, spanning both the Latinate and Germanic traditions. Type-scenes are the recurring, stock scenes comprising the basic structure and cognitive guidance for narrative. These formulaic scenes enabled medieval poets to express originality while honoring tradition. Central to medieval poetic invention, type-scenes form the vital "internal organs" of narrative, each serving a specialized function while working in concert with other organs to create and sustain the story. This accessible and engaging guide to medieval type-scenes consists of three parts: Part One is a Compendium of the type-scenes commonly found in medieval narrative, including analyses of examples from individual poems. Part Two explores combinations of type-scenes within single works of literature for purposes of chronology, characterization, or virtuosity. Part Three examines how a single type-scene manifests across multiple poems, adapting to a variety of settings and periods, while maintaining its original intent. This volume kindles in scholars, teachers and students alike a new and refreshing awareness of the foundational narrative strategies of medieval literature"--
Includes bibliographical references and index.
Keywords: Literature, Medieval -- History and criticism; Narration (Rhetoric); Literary criticism